2007
DOI: 10.4049/jimmunol.179.2.1039
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Expansion of Human Virus-Specific FoxP3− Effector Memory and De Novo-Generated FoxP3+ Regulatory CD8+ T Cells upon Antigen Recognition In Vitro

Abstract: Although FoxP3 has been shown to be the most specific marker for regulatory CD4+ T cells, its significance in the CD8+ T cell population is not well understood. In this study, we show that the in vitro stimulation of human PBMC with hepatitis C virus or Flu virus-specific peptides gives rise to two distinct Ag-specific T cell populations: FoxP3− and FoxP3+CD8+ T cells. The FoxP3+ virus-specific CD8+ T cells share phenotypical markers of regulatory T cells, such as CTLA-4 and glucocorticoid-induced TNFR family-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 45 publications
2
69
1
4
Order By: Relevance
“…Although Foxp3 is not a very specific marker for regulatory T cells given that activated nonregulatory T cells may transiently upregulate this transcription factor (34,35), several reports and current data described that regulatory T cells mediate tolerance to NIMA (31,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although Foxp3 is not a very specific marker for regulatory T cells given that activated nonregulatory T cells may transiently upregulate this transcription factor (34,35), several reports and current data described that regulatory T cells mediate tolerance to NIMA (31,36).…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs were stimulated and analysed as described previously (Billerbeck et al, 2007) by using Tetramer and antibody staining, and intracellular FoxP3 staining. Cells were stained with HLA-A2 tetramers and surface antibodies as described previously (Billerbeck et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…PBMCs were stimulated and analysed as described previously (Billerbeck et al, 2007) by using Tetramer and antibody staining, and intracellular FoxP3 staining. Cells were stained with HLA-A2 tetramers and surface antibodies as described previously (Billerbeck et al, 2007). Intracellular FoxP3 staining was performed by using the eBioscience FoxP3 staining buffer set for antibody PCH101 or the BioLegend FoxP3 Flow kit for antibody 259D according to the manufacturers' instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that CD8ϩ cells from patients with chronic HCV infection may express FoxP3 after stimulation with HCV-derived peptides, which indicates that there is likely a wide heterogeneity of FoxP3-expressing cells in response to viral infection (30). Moreover, our finding that a complete response to treatment with PEGylated interferon alfa-2b plus ribavirin was associated with a decrease in T cell activation, contrasts to some degree with previous studies in patients with chronic HCV infection without MC, which showed that treatment with interferon plus ribavirin induced an increase in T cell activation markers (HLAϪDRϩ and CD25ϩ) after treatment (31), as well as a shift toward a Th1-type response (32)(33)(34).…”
mentioning
confidence: 99%